2022
DOI: 10.1177/1086296x221140852
|View full text |Cite
|
Sign up to set email alerts
|

Girls of Color Embodied and Experiential Dreams for Education

Abstract: Through an exploration of an afterschool writing club for middle school girls of Color (GOC), this article puts forth the argument that GOC consistently leverage incisive critiques of schooling through multiple literacies, including embodied and experiential ways of knowing and communicating. However, oftentimes, these critiques are ignored because their literacies are marginalized, ignored, and misread. As informed by their lived and felt experiences, it becomes apparent how school has failed them and how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The mentor and mentee relationship is similar to a familial relationship, that of a hermandad [sisterhood], in which we strive to support our escritoras in accomplishing their goals and developing personally and academically. This is central to feminist-mujercentered spaces where mentors celebrate the brilliance, genius, creativity, and fight of Black and Brown Girls and Youth of Color (Muhammad, 2014;Brown, 2013;Player, 2022).…”
Section: Composingmentioning
confidence: 99%
See 1 more Smart Citation
“…The mentor and mentee relationship is similar to a familial relationship, that of a hermandad [sisterhood], in which we strive to support our escritoras in accomplishing their goals and developing personally and academically. This is central to feminist-mujercentered spaces where mentors celebrate the brilliance, genius, creativity, and fight of Black and Brown Girls and Youth of Color (Muhammad, 2014;Brown, 2013;Player, 2022).…”
Section: Composingmentioning
confidence: 99%
“…Community-embedded scholars have documented the transformative and worldchanging power of intentionally designed arts-based and literacy spaces that center on the rich cultural, linguistic, and familial assets of Girls and Youth of Color (García and Gaddes, 2012;Guti errez, 2008;Lee et al, 2022;Muhammad, 2012Muhammad, , 2014Player, 2022;Wissman, 2011). In these spaces, Girls and Youth of Color join in community to examine their histories by reading and discussing culturally relevant texts rooted in their experiences, composing personal narratives, and engaging in various performative acts.…”
mentioning
confidence: 99%
“…Moving beyond a view of literacy as a decontextualized act of reading and writing the printed word, multiliteracies acknowledges the multiple modes (oral, aural, gestural, linguistic, spatial, and multimodal) available for expressing and generating meaning (for more on multimodal theory, see Kress, 2009). Multiliteracies theory has enabled scholars to focus on the relationships between literacies and identities, showing, for example, how literacy is connected to gender, sexuality and sexual orientation, race, and culture (Blackburn, 2003;Leent & Mills, 2018;Player, 2022;Price-Dennis et al, 2017;Reid, 2022), and it has generated a groundswell of research aimed at understanding how literacy learning occurs across dynamic outside-school contexts, both local and global, in which people engage in their self-sponsored literacies and embrace a range of social processes and cultural practices. This area of research, with its heavy focus on school-age youth, has identified important features of learning environments that are inclusive of and further build youth literacies (Cope & Kalantzis, 2005de los Ríos, 2018;Nash & Brady, 2022;Skerrett & Bomer, 2011, 2013.…”
Section: Multiliteraciesmentioning
confidence: 99%
“…A broad body of literature on out-of-school literacy in the United States has attended to youths' writing practices, addressing family and home literacies (Segel, 2023), informal or youth-led literacies (Shrodes, 2022), and formal groups or after-school literacy settings (Player, 2022). Out-of-school spaces can potentially foster writing practices that are not always valued in schools, including participatory and collaborative writing (e.g., wiki writing or fan fiction; see Curwood et al, 2013), translanguaging and multilingual writing (Gallo & Corral, 2023), and performed or dramatic writing (Lenters & Smith, 2018).…”
Section: Introductionmentioning
confidence: 99%